Structural and dielectric characterization of praseodymium-modified lead titanate ceramics synthesized by the OPM route - Pinto, Alexandre H.; Souza, Flavio L.; Longo, Elson [UNESP]; Leite, Edson R.; Camargo, Emerson R. (Elsevier B.V. Sa, 2011)
Quasi-spherical nanoparticles of praseodymium-modified lead titanate powder (Pb(0.80)Pr(0.20)TiO(3)) with an average size of 54.8 nm were synthesized successfully by the oxidant-peroxo method (OPM) and were used to prepare highly dense ceramic bodies which were sintered at 1100 and 1150 degrees C for 2 h. A tetragonal phase was identified in the powder and ceramic samples by X-ray powder diffraction and FT-Raman spectroscopy at room temperature. The fractured surface of the ceramic sample showed a high degree of densification with fairly uniform grain sizes. Dielectric constants measured in the range of 30-300 degrees C at different frequencies (120 Hz and at 1,10 and 100 kHz) indicated that samples with 20 mol% praseodymium showed normal ferroelectric behavior regardless of the sintering temperature. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Oxides; Ceramics; Chemical synthesis; Dielectric properties